2020
DOI: 10.3892/ol.2020.11257
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of APOBEC3G expression with liver function indexes of patients with chronic hepatitis B and comparison in chronic hepatitis B, liver cirrhosis and liver cancer

Abstract: Correlation of APOBEC3G expression with liver function indexes of patients with chronic hepatitis B and its expression in chronic hepatitis B, liver cirrhosis and liver cancer were investigated to evaluated the significance of APOBEC3G. Fifty-eight patients with chronic hepatitis B were selected, including 20 cases of chronic hepatitis B, 19 cases of liver cirrhosis and 19 cases of liver cancer. Liver function indexes were detected and analyzed, and messenger ribonucleic acid (mRNA) and protein expression leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…During alanine aminotransferase (ALT) flare-up in HBV carriers, G-to-A hypermutation of HBV increased [ 40 ]. Moreover, A3G mRNA in liver tissues is moderately associated with the ALT content [ 41 ]. These controversial findings surrounding A3G levels in chronic HBV infection need further investigation with a large number of samples.…”
Section: A3 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…During alanine aminotransferase (ALT) flare-up in HBV carriers, G-to-A hypermutation of HBV increased [ 40 ]. Moreover, A3G mRNA in liver tissues is moderately associated with the ALT content [ 41 ]. These controversial findings surrounding A3G levels in chronic HBV infection need further investigation with a large number of samples.…”
Section: A3 Expressionmentioning
confidence: 99%
“…Multiple approaches confirmed that the content of A3G in liver tissues was the highest in CHB patients, slightly lower in patients with liver cirrhosis and the lowest in liver cancer [ 41 ]. No significant difference in liver A3G products was found between CHB patients and HCC patients in another report [ 38 ].…”
Section: A3 Expressionmentioning
confidence: 99%
“…Comparison of general information between the two groups (n (%), x ± s). AST), total bilirubin (TBIL), and total bile acid (TBA)[10][11][12].…”
mentioning
confidence: 99%